Childhood, passages for a learning flaneur - Sanches, Eduardo Oliveira; Silva, Divino Jose da [UNESP] (Univ Federal Santa Maria, 2019)
This theoretical study aims to analyze the Beaminian images of flaneur and childhood, approaching them, to reflect on the idea of an apprentice flaneur as a figure who keeps alive in his perception of the world a sensitivity that refuses linear discourse, Which leads him to the indirect path in relation to the knowable objects. From these deviations emerges the aura of things, from which one can have the possible experience with the modern; The sensitivity of the child as equivalent to that of a flaneur; And an understanding of the culture of the child, being constituted, in part, from the remains of history, on the margins of adult culture, in another, by the deviations originated by the child's action in its protagonism. The protagonism of the child and the deviant mode as it approaches the things of the world endow the same ability of the flaneur, according to the possibilities of the child, which brings us the idea of the apprentice flaneur. In terms of method, the threshold formed by the approximation and play of images between these two figures has the potential to amplify the understanding and importance of both the image of the flaneur and the notion of childhood in Walter Benjamin's work.
Keywords: Childhood; Flaneur; Culture of the child